Corrigendum: Urban Decay in Central Hill, Port Elizabeth (IOP Conf. Ser.: Earth Environ. Sci.290 012127). (21st June 2019) - Swanepoel, F; Smallwood, J
Abstract: The text of the corrigendum is available in the PDF. Corrigendum published: 8 November 2019